ACCESS TO HEALTHCARE FOR PEOPLE IN HOMELESS SITUATIONS (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2024)
This research is a literature review that addresses the impossibility often experienced by homeless people without access to health. The homeless population (PSR) suffers, in many cases, deprivation of rights, which contributes to social exclusion and marginalization. This impossibility of PSR accessing public health services goes against the concepts of universality, equity and integrality of the Unified Health System – SUS. The right of access to health for the homeless puts into effect the concept of democracy itself, because if all individuals are sovereign, social exclusion goes against the grain of democracy itself. As a way of guaranteeing health for the entire population, the Federal Constitution established the Unified Health System (SUS) as a fundamental right, which, through public policies, makes political decisions with the objective of offering services to the population in general. , thus including those present in minorities and vulnerable groups. The current health system is presented, discussing what is necessary to guarantee the rights of these citizens through public policies, bringing the possibility of implementing a health system that works with intersectoriality for public policies, working jointly health, social assistance, housing, among others. With this measure, it is possible to carry out a work of social reintegration of the homeless population, so that they can recover their citizenship.